2019
DOI: 10.31367/2079-8725-2019-62-2-21-26
|View full text |Cite
|
Sign up to set email alerts
|

Technological and Bread Baking Traits of Triticale

Abstract: Winter triticale, carrying the genes of its parental forms, has taken both the positive properties of wheat and rye (a significant amount of protein, presence of gluten, content of biologically active aromatic substances) and negative (a large amount of soluble albumin and globulin proteins and especially high activity of amylolytic enzymes). The weather conditions during the vegetation, as well as the varietal characteristics of this grain crop are of great influence on the grain quality. Therefore, cultivati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 2 publications
1
1
1
Order By: Relevance
“…This flour does provide bread of consistently standard quality and needs to be subgraded to wheat flour. The results obtained confirm the data of other researchers (Gyori, 2018;Kalnina et al, 2015;Shabolkina et al, 2019). The dough's physical properties from triticale flour were determined on the Shopin alveograph (Figure 2).…”
Section: Raw Materials Analysissupporting
confidence: 89%
See 2 more Smart Citations
“…This flour does provide bread of consistently standard quality and needs to be subgraded to wheat flour. The results obtained confirm the data of other researchers (Gyori, 2018;Kalnina et al, 2015;Shabolkina et al, 2019). The dough's physical properties from triticale flour were determined on the Shopin alveograph (Figure 2).…”
Section: Raw Materials Analysissupporting
confidence: 89%
“…The growing region largely determines the biochemical properties. Thus, Shabolkina et al (2019), who analyzed a large number of Volga triticale varieties, concluded that under favorable growth and development conditions, winter triticale accumulates a significant amount of protein (18.3%-18.8%), forms a grain with strong starch and low enzymatic activity: the "fall number" is 252-274 s. These indicators are significantly better than those obtained in our studies. However, these authors also claim that due to the low gas-retaining quality and dough dilution, triticale is not recommended for bread making without wheat flour subgrading.…”
Section: Raw Materials Analysiscontrasting
confidence: 60%
See 1 more Smart Citation